A swan-sized fossil anatid (Aves: Anatidae) from the early Miocene St Bathans Fauna of New Zealand - Worthy, Trevor H.; Scofield, R. Paul; Hand, Suzanne J.; de Pietri, Vanesa L.; Archer, Michael (Zootaxa, 2022)
A large fossil anserine-like anatid (Aves, Anatidae, Notochen bannockburnensis gen. et sp. nov.) is described based on a distal humerus from the lower Bannockburn Formation, early Miocene (19–16 Ma), St Bathans Fauna from New Zealand. Its morphology and size suggest that this taxon represents an early swan rather than a goose. Extant anserines are split into Northern and Southern Hemisphere clades. The St Bathans Fauna is known to have the oldest anserines in the Southern Hemisphere, unnamed cereopsines perhaps ancestral to species of Cnemiornis (New Zealand geese). The elongate and flat morphology of the tuberculum supracondylare ventrale of the new species, however, preclude affinities with cereopsines. It is a rare taxon and the eighth anatid represented in the fauna and is the largest known anseriform from the Oligo-Miocene of Australasia. We also reassess other large anatid specimens from the St Bathans Fauna and identify Miotadorna catrionae Tennyson, Greer, Lubbe, Marx, Richards, Giovanardi & Rawlence, 2022 as a junior synonym of Miotadorna sanctibathansi Worthy, Tennyson, Jones, McNamara & Douglas, 2007.